Quantitative characterization of the carbonate rock microstructure considering topological features: a case study from the Gaoshiti–Moxi block of the Sichuan Basin - Dong, Huaimin; Luo, Bin; Dang, Chenyue; Xu, Shuang; Wang, Feng; Chi, Peng (Frontiers in Earth Science, 2024)
Precise characterization of the rock microstructure is crucial for predicting the physical characteristics, flow behavior and mechanical properties of rocks. This is particularly important for carbonate rocks, which depict a complex microstructure with multimodal pore radius distribution and natural fractures. Here, topological features that are typically ignored are taken into account to quantify the carbonate microstructure. Carbonate samples used are from Gaoshiti-Moxi block of Sichuan Basin, which shown remarkable potential for oil and gas. Specifically, nuclear magnetic resonance (NMR), X-ray micro-computed tomography (micro-CT), and mercury injection capillary pressure (MICP) techniques are performed to describe the topological and geometric characteristics. The results indicate that NMR and MICP techniques can describe more rock pores than micro-CT. However, due to the presence of pore shielding in MICP tests, the pore radius gotten by MICP is smaller than those obtained by micro-CT and NMR. Furthermore, the effective method for characterizing the pore structure is NMR technology. The hardest part is that the coefficient between the pore radius and the T2 relaxation time is difficult to calculate. Therefore, a better calculation method must be found. Besides, micro-CT is an irreplaceable technique for obtaining a large number of topological and geometric features, and the multi-phase or single-phase flow simulations can be conducted via digital rock models. For carbonates, however, micro-CT is not sufficient to describe the complete pore systems, owing to macropores cannot be fully represented and sub-resolution micropores cannot be descripted. Actually, those macropores and micropores have a very important effect on their seepage properties. Therefore, the multi-scale digital rock modeling involving small and large pores is essential for complex rocks, which is of great significance for the analysis of pore systems and the simulation of rock physical properties.